KEBERMAKNAAN KOMPETENSI DAN DISIPLIN KERJA DALAM MENINGKATKAN KINERJA PEGAWAI - Sri Wahyuni; Herman Sjahruddin; Abd. Rajab (Jurnal Bina Bangsa Ekonomika, 2024)
This research aims to confirm the effect of competency and work discipline on civil servant performance at the PUPR Region VIII Makassar Competency Development Center. The technique used in sampling is a total sampling technique so there are 45 employees as the unit of analysis. The problem in the research is that there is a decline in civil servant performance on competency development indicators and internal infrastructure services so it is important to analyze them using multiple regression analysis. The test results provide evidence that the decline in civil servant performance is not caused by competence and work discipline but by other factors that are not analyzed, because the test results provide evidence that the civil servant competence and work discipline are at a high level so they are proven to be able to increase their performance to a higher level